Emergency Physicians’ Knowledge and Attitudes Towards Childhood Traumatic Tooth Avulsion in Turkey: A Multicenter Questionnaire-Based Cross-Sectional Study - Basak Kızıltan Eliacik; Burcu Genc Yavuz (Haseki Tıp Bülteni, 2021)

(untitled)
Aim:In children presenting to the emergency room with traumatic tooth avulsion (TTA), the immediate replantation of the avulsed permanent tooth is required. We study aimed to investigate the knowledge and attitude of emergency physicians (ER) regarding emergency management of avulsed teeth.Methods:This multi-center cross-sectional survey study was conducted from October to December 2020. A self-administered questionnaire that had been designed in the Internet environment was sent to directors of ER facilities in hospitals regarding physicians at the emergency room in the hospitals. A total of 381 physicians participated by filling out the questionnaire.Results:Data revealed that 92.1 % of the participants did not find prior knowledge sufficient about avulsion and only 8.9% would replant the tooth by themselves. 56.2% of the physicians did not know the importance of tetanus prophylaxis. Only 48% of the participants selected the best transport media for an avulsed tooth. Experienced physicians and the emergency specialist had significantly better knowledge about the management of avulsed teeth (p=0.005 and p<0.001, respectively).Conclusion:The knowledge of avulsed teeth among emergency physicians in Turkey ranges from low to moderate, which highlights the need to improve the knowledge of the management of traumatic dental injuries among emergency physicians.